The role of self-presentation in sharing online content through social media - Pradipta, Harry (2011)
As social media enhances the way consumers are able to interact with each other, companies are pushed to acquire a deeper understanding of consumers’ behaviors in social media. In an attempt to contribute to companies’ understanding as to why and how consumers’ choose to spread information through social media, this study focuses on the role of self-presentation in the process sharing online content in social media applications. The data reveals findings primarily related to two main issues, namely the role of self-presentation and how it affects users’ decisions in sharing online content through social media, based on the views of the users; and the common strategies involved in users’ self-presentation in the process of sharing online content through social media.